Superhydrophobic Surface With Shape Memory Micro/Nanostructure and Its Application in Rewritable Chip for Droplet Storage - Lv, Tong; Cheng, Zhongjun; Zhang, Dongjie; Zhang, Enshuang; Zhao, Qianlong; Liu, Yuyan; Jiang, Lei (ACS nano, 2016)
Recently, superhydrophobic surfaces with tunable wettability have aroused much attention. Noticeably, almost all present smart performances rely on the variation of surface chemistry on static micro/nanostructure, to obtain a surface with dynamically tunable micro/nanostructure, especially that can memorize and keep different micro/nanostructures and related wettabilities, is still a challenge. Herein, by creating micro/nanostructured arrays on shape memory polymer, a superhydrophobic surface that has shape memory ability in changing and recovering its hierarchical structures and related wettabilities was reported. Meanwhile, the surface was successfully used in the rewritable functional chip for droplet storage by designing microstructure-dependent patterns, which breaks through current research that structure patterns cannot be reprogrammed. This article advances a superhydrophobic surface with shape memory hierarchical structure and the application in rewritable functional chip, which could start some fresh ideas for the development of smart superhydrophobic surface.